Socioeconomic inequalities in urban and transport planning related exposures and mortality: A health impact assessment study for Bradford, UK. (December 2018) - Mueller, Natalie; Rojas-Rueda, David; Khreis, Haneen; Cirach, Marta; Milà, Carles; Espinosa, Ana; Foraster, Maria; McEachan, Rosemary R.C.; Kelly, Brian; Wright, John; Nieuwenhuijsen, Mark
Abstract: Background: Cities have unique geographic, environmental and sociocultural characteristics that influence the health status of their citizens. Identification and modification of these characteristics may help to promote healthier cities. Objective: We estimated premature mortality impacts of breaching international exposure guidelines for physical activity (PA), air pollution, noise and access to green space for Bradford (UK) adult residents ( n = 393, 091). Methods: We applied the Urban and TranspOrt Planning Health Impact Assessment (UTOPHIA) methodology and estimated mortality, life expectancy (LE) and economic impacts of non-compliance with recommended exposure levels. We also investigated the distribution of the mortality burden among the population, focusing on socioeconomic position (SEP) as defined by deprivation status and ethnicity. Results: We estimated that annually almost 10% of premature mortality (i.e. 375 deaths, 95% CI: 276–474) in Bradford is attributable to non-compliance with recommended exposure levels. Non-compliance was also estimated to result in over 300 days of LE lost (95% CI: 238–432), which translated in economic losses of over £50, 000 per person (95% CI: 38, 518–69, 991). 90% of the premature mortality impact resulted from insufficient PA performance. Air and noise pollution and the lack of green space had smaller impacts (i.e. 48 deaths). Residents of lower SEP neighborhoods had the highest risks for adverse exposure and premature death. A larger number of deaths (i.e. 253 and 145, respectively) could be prevented by reducing air and noise pollution levels well below the guidelines. Discussion: Current urban and transport planning related exposures result in a considerable health burden that is unequally distributed among the Bradford population. Improvements in urban and transport planning practices including the reduction of motor traffic and the promotion of active transport together with greening of the district, particularly in areas of lower SEP, are promising strategies to increase PA performance and reduce harmful environmental exposures. Highlights: 10% of mortality in Bradford is attributable to breaching physical activity, air pollution, noise and green space guidelines. Residents of lower socioeconomic position neighborhoods had the highest risks for adverse exposure and premature death. Reduction of motor traffic, the promotion of active transport and greening of the district are recommended. Interventions should focus on lower socioeconomic position neighborhoods as the largest health gains are expected there.